Plataforma agregadora para recursos energéticos distribuídos - Raguzzoni, Jeann Carlo Martins (2022)
For many years our energy distribution system structure has been virtually the same, particularly for the consumer. With the arrival of advanced metering equipment, renewable energy implementations and other distributed energy resources, a sudden change begins to happen, requiring that both consumer and the provider sides to adapt. Those changes have an impact in many areas, be them be related to how the consumers are charged, new equipment to replace old ones, legislation, collection and data analysis, among other changes. The distributed energy resources alongside consumers that can now be called prosumers now bring a new paradigm for the energy distribution system and require better accuracy in relation to the data that is being generated and stored. These new energy resources are diverse, such as photovoltaic panels, battery storage systems, electric vehicles and may imply on a bidirectional flow of energy. All of those changes cause different kinds of impact over the electric grid and consequentially over the kind of data that is being generated. This master thesis looks to address the difficulties and necessities that exist on connecting different kind of distributed energy resources to a smart grid. This work proposes a solution that allows the integration of many load, generation and storage resources located on the consumer side to the operation side of the smart grid, resulting in a software and hardware implementation. Finally, at the end an aggregator platform for distributed energy resources is developed to integrate distinct equipment in a single place, so that they can communicate transparently with each other, allowing for many others kind of applications on the smart grid, such as demand response algorithms and smart contracts.